INSIGHTFUL CORPORA WITH APPLIED TO ELT-CALL BETWEEN THE LINE OF LEARNING AND TEACHING IN COMPUTATIONAL LINGUISTICS - G K, Chithra; .V, Saravanan; .T, Anandkrishnan; Nanjangud Gopalkrishna, Nagakala (International Journal of Psychosocial Rehabilitation, 2020)
This paper is pragmatically connected up with the Corpora and Classroom concordance-connected empirical issue of ELT-CALL in terms of planning to understand and training below the dynamic domain of underlying data-driven learning (DDL) exercise within the reach of Corpora-based investigation within the linguistics atmosphere. To unearth the groundbreaking reality of the middle productive price of Corpus, schoolroom concordance, and data-driven planning to understand, multiple ELT and CALL are entirely relayed on the pedagogic Corpora part, and capability expands with planning to understand and training in an exceedingly academic productive doable final leads to an even bigger extent. Therefore, this paper is obstinately inherent in perceptive Corpora concordance with sound clever utilitarian educational impact of learning and teaching in multi-dimensional method of data-driven mastering workout still as data-driven teaching workout via software system program concordance. This paper has nearly delivered out the exceptional monumental actual center price of Corpora (school area concordance) all-told varieties of ELTCALL component that’s intently encompassed with pedagogic scope in terms of process linguistic (CL).